Radiopasteurisasi ikan tenggiri (Scomberomorus Spp.) - Siagian, E. G. (Badan Tenaga Atom Nasional, Pusat Penelitian Ps Djum'at, 1970)
Radio pasteurization of scomberomorus spp., to prolong resistance against decay of species during storage.